2017
DOI: 10.1002/ajpa.23189
|View full text |Cite
|
Sign up to set email alerts
|

Testing biomechanical models of human lumbar lordosis variability

Abstract: Hip moments appear constrained suggesting the possibility of selection, and the beam model explains some LL variability due to variations in trunk geometry. The strength-flexibility interaction best predicted LL, suggesting a tradeoff in which ROM limits the effects of back strength on LL. The strength-flexibility model may have clinical relevance for spinal alignment and pathology. This model may also suggest that straight-backed Neanderthals had reduced lumbar mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…1). The size-standardized central angle method has been shown to measure lumbar curvature reliably, correlating strongly with standard radiological techniques for quantifying LL including Cobb angle (Castillo et al, 2017). The central angle, which also allows for dynamic measures of LL during in vivo experimental studies, is calculated as the ratio of the curved arc length of the lumbar spine divided by its radius of curvature.…”
Section: Kinematicsmentioning
confidence: 94%
See 3 more Smart Citations
“…1). The size-standardized central angle method has been shown to measure lumbar curvature reliably, correlating strongly with standard radiological techniques for quantifying LL including Cobb angle (Castillo et al, 2017). The central angle, which also allows for dynamic measures of LL during in vivo experimental studies, is calculated as the ratio of the curved arc length of the lumbar spine divided by its radius of curvature.…”
Section: Kinematicsmentioning
confidence: 94%
“…Study participants were recruited from the greater Boston area for a series of three experiments conducted on different days over the course of 4 months (see Castillo et al, 2017). Only young adults 18-35 years old were recruited to minimize the potential for age-related degenerative changes in spinal posture (Schwab et al, 2006).…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, flexibility training should be a priority for wheelchair athletes. A recent study by Castillo et al [5] demonstrated how lumbar mobility differentially interacts with trunk strength to affect lordotic curvature. If changes in relative trunk strength and ROM change lumbar lordosis within an individual, this study suggests that exercises to strengthen the abdominal or back muscles are more likely to be effective at modifying spinal posture in individuals with naturally flexible lumbar spines, or when muscle strengthening is accompanied by stretching to increase lumbar ROM.…”
Section: Discussionmentioning
confidence: 99%